(untitled) (Actaeducation, 2024)
The positioning of any economy in the global light is anchored on the growth and development of its educational institutions hence the more developed these institutions are, the more advanced such economy will be to handle issues related to technological advancements, development of military arsenals, robust & global economy and scientific breakthroughs et. The performance of these institutions is dependent on the impact of both informal and formal education on the academic performance of students influenced by certain key factors amongst which includes; Socio-economic Status (SES) and Interest. This paper seeks not to only investigate the impact of these two factors but also observe amongst them which has a greater impact on academic performance while steering its attention on two core subjects; Mathematics and English Language. On this premises, let’s consider the performance of 210 students in the Senior Secondary One (SS1) spanning across six (6) different Schools within the city of Jos. The data collected were analyzed and tabulated using Microsoft Excel. Results showed that though both factors impact academic performance (either positively or negatively) however SES seems to have a much greater influence on academic performance than interest.